2015
DOI: 10.1039/c5ra09816e
|View full text |Cite
|
Sign up to set email alerts
|

Conductive properties and mechanisms of different polymers doped by carbon nanotube/polypyrrole 1D hybrid nanotubes

Abstract: We suggested a method to reduce the amount of multi-walled carbon nanotubes (MWNTs) for fabricating polymer composites, and revealed the electron transport mechanism in polymer matrixes with different polarity. Specifically, onedimension (1 D) hybrid nanotubes (MPPy) have been easily prepared by in-situ polymerization with appropriate ratio of pyrrole to MWNTs. Three matrixes including polyvinyl chloride (PVC), poly (methyl methacrylate) (PMMA) and polystyrene (PS) were separately mechanical blending with MPPy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…In a percolating system, we might expect both carrier density and mobility follow percolation-like scaling laws. While this has not been reported to our knowledge, reanalysing the data of Tan et al 39 shows this to be approximately true. Assuming this is the case, we can write:…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In a percolating system, we might expect both carrier density and mobility follow percolation-like scaling laws. While this has not been reported to our knowledge, reanalysing the data of Tan et al 39 shows this to be approximately true. Assuming this is the case, we can write:…”
Section: Discussionmentioning
confidence: 58%
“…To explain this, we consider both dark and illuminated composite conductivity in In the dark, we expect both mobility (D) and carrier density (nD) to increase with graphene content, 39 with the mobility increase due to the effect of graphene on transit time described above. 20 However, we must also consider that the graphene sheets will almost certainly be slightly doped due to their interaction with the environment (residual solvent etc) and so will have a much higher free carrier density than the MoS2, leading to an increase in the effective carrier density as graphene content increases.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure , the resistivity values in nanocomposites are considerably smaller than that of the RGO–PAMAM, and they gradually decrease with increasing content of Ag nanoparticles, and the nanocomposites with lower‐generation PAMAM would obtain the best conductivity at the same added content of Ag. Among these nanocomposites, the 33%Ag‐r‐RGO‐G1.0 achieves the minimum value of 0.17 Ω cm (or 5.88 S cm −1 ), which is higher than that reported in the literature . In general, the charges are carried mainly via free electrons or holes in the composites, and this process is hindered on account of the absent conjugated structure in PAMAM dendrimers.…”
Section: Resultsmentioning
confidence: 69%
“…Among these nanocomposites, the 33%Ag-r-RGO-G1.0 achieves the minimum value of 0.17 X cm (or 5.88 S cm 21 ), which is higher than that reported in the literature. [58][59][60] In general, the charges are carried mainly via free electrons or holes in the composites, and this process is hindered on account of the absent conjugated structure in PAMAM dendrimers. Nevertheless, the migration of electric charges experiences a dramatic reinforcement arising from the Ag NPs uniformly stabilized on the surface of global dendrimers, which provide a beneficial conductive path with charge carriers, and the mobility of charge carriers is more efficient with the lower-generation PAMAM dendrimers on account of a lower degree of branching.…”
Section: Performance Analysis Of Ag-r-rgo-pamam Nanocompositesmentioning
confidence: 99%
“…It was reported that three matrixes of polyvinyl chloride, poly(methyl methacrylate), and PS that were separately mechanical blended with one‐dimensional hybrid nanotubes achieved electrical conductivity of higher than 10 −5 S/cm . Also, synthesis of conduction polymer, poly( o ‐toluidine), and silver nanoparticles nanocomposites exhibited electrical conductivity of 1.28 S/cm .…”
Section: Resultsmentioning
confidence: 99%